Macroprudential Regulation - What, Why and How? - Henrik Borchgrevink; Sigmund Ellingsrud; Frank Hansen (Norges Bank, 2014)
This paper reviews recent literature on the theoretical foundations of macroprudential regulation. We identify six categories of market failures that give rise to macroprudential concerns; pecuniary externalities, interconnectedness externalities, strategic complementarities, aggregate demand externalities, market for lemons and deviations from full rationality. Because of the diversity of these categories, policy lessons diverge. There is yet no "workhorse" model for policy analysis. Nevertheless, we argue that two consensus pieces of general policy advice can be drawn from the core part of the literature on macroprudential regulation: First, the intensity of capital and liquidity regulation of banks should also depend on aggregate measures of risk in the financial system. Second, excessive borrowing should be curbed by a time-varying policy inducing borrowers to internalise the increased risk of a costly deleveraging process in the economy.
hdl:11250/2506905
Keywords: 330